Characterisation of PMMA/ATH Layers Realised by Means of Atmospheric Pressure Plasma Powder Deposition - Lena M. Wallenhorst; Sebastian Dahle; Matej Vovk; Lisa Wurlitzer; Leander Loewenthal; Nils Mainusch; Christoph Gerhard; Wolfgang Viöl (Advances in Condensed Matter Physics)
We report on the characteristics of aluminium trihydrate filled poly(methyl methacrylate) composite (PMMA/ATH) coatings realised by plasma deposition at atmospheric pressure. For this purpose, PMMA/ATH powder was fed to a plasma jet where the process and carrier gas was compressed air. The deposited coatings were investigated by X-ray photoelectron spectroscopy and water contact angle measurements. Further, the raw material was characterised before deposition. It was found that, with respect to the raw material, aluminium was uncovered in the course of the plasma deposition process which can be explained by plasma-induced etching of the PMMA matrix. As a result, the wettability of plasma-deposited PMMA/ATH was significantly increased. Even though a uniform coating film could not be realised as ascertained by confocal laser scanning microscopy, the deposited coatings feature notably enhanced characteristics which could be advantageous for further processing.